Artificial Intelligence-Powered Digital Streamers in Online Retail: Empirical Insights and Design Strategies from Experiments - Liu, Yahui; Wang, Lei; Yang, Shuai; Wang, Yanwen (Information Systems Research, 2026)
As artificial intelligence (AI)-powered digital streamers gain popularity in live commerce, online retailers face critical questions about the actual business value of their operations. This study offers timely, evidence-based insights into the economic impact and optimal design of digital streamers. Although current designs do not significantly improve sales over no live streaming, incorporating behavioral realism—especially enhanced real-time question and answer (Q&A)—can boost sales by 25%, making digital streamers as effective as human hosts. Visual upgrades and human-like voices also help but to a lesser degree. Importantly, not all AI-driven enhancements deliver immediate returns, and imitating human scripts does not guarantee success. Retailers should focus on dynamic human-AI interaction features that drive engagement and trust, such as real-time Q&A and interactive giveaways. Designers are encouraged to integrate multiple realism features to maximize effectiveness while managing cost and scalability. These findings offer actionable guidance for retailers and platform designers seeking to leverage AI effectively and cost efficiently in live streaming commerce.